Healthy dietary patterns improve sexual function and incontinence symptoms: systematic review and meta-analysis of dietary patterns and dietary interventions - Xing, Daiwen; Li, Min; Zhong, Yifei; Liang, Lin; Yao, Huiqing; Liang, Yaxin; Lyu, Yuhan; Yu, Yue (Frontiers in Nutrition, 2025)
BackgroundPelvic floor dysfunction (PFD) primarily including urinary incontinence, fecal incontinence, and sexual dysfunction, significantly impairs individuals’ quality of life. While healthy dietary patterns are considered potential modulators, a synthesized understanding of their impact is lacking.ObjectiveThis systematic study aims to assess the effects of various healthy dietary patterns on PFD, providing a scientific basis for developing effective dietary intervention strategies in clinical practice.MethodsFollowing PRISMA guidelines, we systematically searched PubMed, Web of Sciences, and Embase databases. A total of 493 articles were identified across the five evidence-based dietary patterns: DASH, Mediterranean diet, hPDI, anti-inflammatory diet, and pro-inflammatory diet. After screening titles and abstracts, 196 articles were selected for full-text review, and 31 studies met the criteria. Of these, 14 studies provided sufficient quantitative data and were ultimately included in the meta-analysis. Statistical analyses, including odds ratios (OR) for cross-sectional studies and standardized mean differences (SMD) for prospective studies, were conducted using Review manager version 5.4.ResultsThis study included 10 prospective studies, 17 cross-sectional studies, and 4 randomized controlled trials (RCTs) that recruited diabetic patients, patients with urinary incontinence, and other populations from North America, Europe, Asia, and other regions. The findings showed that healthy dietary patterns significantly improved sexual dysfunction (cross-sectional studies: OR = 0.69, 95% CI [0.55, 0.85]; prospective studies: SMD = −0.6, 95% CI [−1.02, −0.17]) and incontinence symptoms (cross-sectional studies: OR = 0.77, 95% CI [0.68, 0.87]). Specially, the Mediterranean diet and anti-inflammatory dietary patterns were significantly associated with a reduced risk of sexual dysfunction. The DASH diet was effective in alleviating lower urinary tract symptoms and urgency urinary incontinence. Conversely, pro-inflammatory dietary patterns were significantly associated with an increased risk of urinary and fecal incontinence.ConclusionHealthy, anti-inflammatory dietary patterns, particularly the Mediterranean diet, are associated with significant improvements in Pelvic floor dysfunction, particularly sexual dysfunction and incontinence symptoms. These findings support the integration of dietary counseling into the management of PFD, with a particular focus on patients with co-existing metabolic risk factors.